Alternative Laser Treatment Protocol for Bruise Management - Yi, Kyu‐Ho; Wan, Jovian; Yoon, Song Eun; Pamela, Ruri; Cartier, Hugues; Garson, Sebastien; Ascher, Benjamin (Journal of cosmetic dermatology, 2025)
ABSTRACT Background Post‐procedural ecchymosis can last up to two weeks and diminish patient satisfaction. Laser‐assisted clearance is documented with pulsed‐dye devices, but data on 1064‐nm picosecond/nanosecond platforms remain sparse. Objective To evaluate a staged 1064‐nm laser protocol for accelerating bruise resolution after dermal filler injections. Methods Three women (aged 40–52 years, Fitzpatrick III–IV) with facial bruises were treated on Day 2–3 using a picosecond 1064‐nm Nd:YAG laser (0.20–0.30 J/cm², 8–10 mm spot, 8–10 Hz, 8–10 min). A nanosecond Q‐switched 1064‐nm Nd:YAG session followed on Day 4–7 (2.5–3.0 J, 8 mm spot, 30–40 stacked shots) with peri‐session cooling. Clinical photographs and Global Aesthetic Improvement Scale (GAIS) ratings were obtained through Day 7. Results All bruises faded substantially within 4–5 days; near‐complete resolution was achieved by Day 6–7. GAIS scores were “Much” or “Very Much Improved” in every case. No pain, post‐inflammatory hyperpigmentation, or other adverse effects occurred. Compared with typical spontaneous recovery (≈10–14 days), the protocol shortened visible downtime by 40%–60%. Conclusion A sequential 1064‐nm picosecond–nanosecond regimen appears safe and effective for rapid ecchymosis clearance after aesthetic injections. Larger controlled studies are warranted to optimise fluence, cost‐effectiveness, and applicability to other procedural bruises and darker skin types.